2001
DOI: 10.1002/glia.10004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of P2X7 receptors induced [3H]GABA release from the RBA‐2 type‐2 astrocyte cell line through a Cl/HCO3‐dependent mechanism

Abstract: ATP is an important signaling molecule in the nervous system and it's signaling is mediated through the metabotropic P2Y and ionotropic P2X receptors. ATP is known to stimulate Ca(2+) influx and phospholipase D (PLD) activity in the type-2 astrocyte cell line, RBA-2; in this study, we show that the release of preloaded [(3)H]GABA from RBA-2 cells is mediated through the P2X(7) receptors. ATP and the ATP analogue 3'-O-(4-benoylbenoyl)-adenosine-5'-triphosphate (BzATP) both stimulated [(3)H]GABA release in a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 64 publications
2
51
1
Order By: Relevance
“…Future studies will elucidate the mechanism of the apoptotic cell death mediated by increase in intracellular Cl Ϫ . To our knowledge, Wang et al (39) have only reported the presence of a Cl Ϫ /HCO 3 Ϫ -dependent mechanism in the P2X 7 receptor-induced ␥-aminobutyric acid release from astrocytes, but their system is different from our system in its sensitivity for HCO 3 Ϫ . The role of extracellular Cl Ϫ in the signal transduction pathway of apoptotic cell death by the activation of P2X 7 receptor has not been addressed before.…”
Section: Discussioncontrasting
confidence: 61%
“…Future studies will elucidate the mechanism of the apoptotic cell death mediated by increase in intracellular Cl Ϫ . To our knowledge, Wang et al (39) have only reported the presence of a Cl Ϫ /HCO 3 Ϫ -dependent mechanism in the P2X 7 receptor-induced ␥-aminobutyric acid release from astrocytes, but their system is different from our system in its sensitivity for HCO 3 Ϫ . The role of extracellular Cl Ϫ in the signal transduction pathway of apoptotic cell death by the activation of P2X 7 receptor has not been addressed before.…”
Section: Discussioncontrasting
confidence: 61%
“…When cortical astrocytes were subjected to mechanical strain, ATP was released, leading to Akt activation; PPADS attenuated the Akt activation . ATP can activate P2X 7 receptors in astrocytes to release glutamate, GABA, and ATP, which regulate the excitability of neurons (Wang et al, 2002). ATP release during neuronal excitation or injury can enhance the inflammatory effects of cytokines and prostaglandin E 2 in astrocytes and may contribute to the chronic inflammation seen in Alzheimer's disease (Xu et al, 2003).…”
Section: A Neuroprotectionmentioning
confidence: 99%
“…Although GABA and glutamate release through P2X 7 Rs was reported to occur in astrocytes (Wang et al, 2002;Duan et al, 2003), the only evidence favoring the participation of P2X 7 Rs in ATP release was provided by Ballerini et al (1996). These authors showed that stimulation of rat astrocytes with a P2X 7 R agonist ([2Ј-3Ј-O-(4-Benzoyl-benzoyl) adenosine 5Ј-triphosphate (BzATP)) induced Lucifer yellow (LY) uptake and purine release, whereas the antagonist oxidized ATP (oATP) prevented these responses.…”
Section: Introductionmentioning
confidence: 99%